The Influence of Profitability, Leverage, and Liquidity on Stock Prices in the Food and Beverage Sector Listed on the Indonesia Stock Exchange - Kristin*, Maria Alicia; Nugraeni, Nugraeni (Universitas Syiah Kuala, 2023)
This research was conducted with the aim of examining the influence of profitability, leverage, and liquidity on stock prices in the food and beverage sector companies listed on the Indonesia Stock Exchange during the period 2019-2021. The population consisted of 57 food and beverage sector companies on the Indonesia Stock Exchange. Data collection utilized secondary data, which involved processing the financial reports of food and beverage sector companies for the period 2019-2021. By employing purposive sampling method, this research obtained 32 samples. The research data were analyzed using classic assumption tests and multiple linear regression analysis. The results of this research indicate that profitability has a positive effect on stock prices, leverage has a negative effect on stock prices, and liquidity has a positive effect on stock prices.